2013
DOI: 10.3389/fpsyg.2013.00921
|View full text |Cite
|
Sign up to set email alerts
|

Musical feedback during exercise machine workout enhances mood

Abstract: Music making has a number of beneficial effects for motor tasks compared to passive music listening. Given that recent research suggests that high energy musical activities elevate positive affect more strongly than low energy musical activities, we here investigated a recent method that combined music making with systematically increasing physiological arousal by exercise machine workout. We compared mood and anxiety after two exercise conditions on non-cyclical exercise machines, one with passive music liste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
51
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 39 publications
3
51
1
1
Order By: Relevance
“…The results support the findings of Baldari et al, (2010), who reported that exercising while also getting music therapy reduces anxiety at a greater extent than exercising without music in active participants. The results were in contrast with Macone et al, (2006) who reported that exercising along with musical intervention does not result in reduction of state anxiety; and consistent with the findings of Fritz et al, (2013) who reported that exercising while getting musical feedback enhances the mood status of an individual, and ultimately reduces anxiety. This discrepancy could partly be due to population difference.…”
Section: Discussionsupporting
confidence: 83%
“…The results support the findings of Baldari et al, (2010), who reported that exercising while also getting music therapy reduces anxiety at a greater extent than exercising without music in active participants. The results were in contrast with Macone et al, (2006) who reported that exercising along with musical intervention does not result in reduction of state anxiety; and consistent with the findings of Fritz et al, (2013) who reported that exercising while getting musical feedback enhances the mood status of an individual, and ultimately reduces anxiety. This discrepancy could partly be due to population difference.…”
Section: Discussionsupporting
confidence: 83%
“…The result after intervention in the experimental group shows that music therapy made a highly significant change in their social skills. So it is compatible with the results achieved in previous studies on the effect of music therapy in improving psychological function and resolve of some psychiatric disorders including anxiety and improve stress management [7] [10] [11] [16]- [20]. The effect music therapy on social growth may be due to mood regulation [6]- [8] or by improving function of brain in coping with stress, self-satisfaction and self-confidence increases [13]- [15].…”
Section: Discussionsupporting
confidence: 86%
“…The musical feedback session was recorded 5 days prior to the current experiment. In this music session, participants worked out on fitness machines (stomach trainer, stepper and cable lat pulldown) that were enhanced with sensors and a sound system to produce musical sounds through workout movement (Fritz et al, 2013a , b ). Musical parameters that were modulated by the group were cutoff-filter and pitch of different tracks of a largely predefined musical piece.…”
Section: Methodsmentioning
confidence: 99%
“…When working out, participants created the musical piece in a group performance. This paradigm had previously been shown to be effective at evoking euphoric musical experiences through a combination of musical expression and physical exertion (for a detailed description, see Fritz et al, 2013a , b ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation